Landscape of variable domain of heavy‐chain‐only antibody repertoire from alpaca - Tu, Zhui (Immunology, 2020)
Heavy‐chain‐only antibodies (HCAbs), which are devoid of light chains, have been found naturally occurring in various species including camelids and cartilaginous fish. Because of their high thermostability, refoldability and capacity for cell permeation, the variable regions of the heavy chain of HCAbs (VHHs) have been widely used in diagnosis, bio‐imaging, food safety and therapeutics. Most immunogenetic and functional studies of HCAbs are based on case studies or a limited number of low‐throughput sequencing data. A complete picture derived from more abundant high‐throughput sequencing (HTS) data can help us gain deeper insights. We cloned and sequenced the full‐length coding region of VHHs in Alpaca (Vicugna pacos) via HTS in this study. A new pipeline was developed to conduct an in‐depth analysis of the HCAb repertoires. Various critical features, including the length distribution of complementarity‐determining region 3 (CDR3), V(D)J usage, VJ pairing, germline‐specific mutation rate and germline‐specific scoring profiles (GSSPs), were systematically characterized. The quantitative data show that V(D)J usage and VHH recombination are highly biased. Interestingly, we found that the average CDR3 length of classical VHHs is longer than that of non‐classical ones, whereas the mutation rates are similar in both kinds of VHHs. Finally, GSSPs were built to quantitatively describe and compare sequences that originate from each VJ pair. Overall, this study presents a comprehensive landscape of the HCAb repertoire, which can provide useful guidance for the modeling of somatic hypermutation and the design of novel functional VHHs or VHH repertoires via evolutionary profiles.